2020
DOI: 10.3390/ijerph17186488
|View full text |Cite
|
Sign up to set email alerts
|

Can Multidisciplinary Inpatient and Outpatient Rehabilitation Provide Sufficient Prevention of Disability in Patients with a Brain Tumor?—A Case-Series Report of Two Programs and A Prospective, Observational Clinical Trial

Abstract: Brain tumor (BT) patients have a high incidence of disability due to the effects of the tumor itself or oncological treatment. Despite the incidence of neurological and functional deficits caused by BT, rehabilitation of those patients is not as properly established as in patients with other neurological conditions. The aim of the research was to evaluate the effectiveness of a multidisciplinary rehabilitation, carried out as an out- or in-patient program, as prevention of disability in BT patients. This was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Like the studies evaluating pharmacological interventions, those evaluating nonpharmacological intervention included patients that had received varying treatments including surgery, radiotherapy and/or chemotherapy. Although many of the studies used a combination of several cognitive tests spanning multiple cognitive domains, some studies relied on the use of a single cognitive measure such as the MMSE, 39 Addenbrooke's Cognitive Examination III, 42 or Repeatable Battery for the Assessment of Neuropsychological Status (R‐BANS) 13 ; in the latter study, the R‐BANS was not completed by most patients at follow‐up, and thus, no longer‐term follow‐up data were provided. One study, published in abstract form, did not describe the specific cognitive tests used 11 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Like the studies evaluating pharmacological interventions, those evaluating nonpharmacological intervention included patients that had received varying treatments including surgery, radiotherapy and/or chemotherapy. Although many of the studies used a combination of several cognitive tests spanning multiple cognitive domains, some studies relied on the use of a single cognitive measure such as the MMSE, 39 Addenbrooke's Cognitive Examination III, 42 or Repeatable Battery for the Assessment of Neuropsychological Status (R‐BANS) 13 ; in the latter study, the R‐BANS was not completed by most patients at follow‐up, and thus, no longer‐term follow‐up data were provided. One study, published in abstract form, did not describe the specific cognitive tests used 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 21 nonpharmacological studies identified, 11 were randomised 11–15,18,19,21,37–39 and 10 were nonrandomised 16,17,20,22,40–45 . Most of the nonpharmacological studies evaluated cognitive training or rehabilitation programmes 11–18,22,38–41,43,44 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, in four articles, setting goals with patients based on information collected from patients and families were addressed. [28][29][30][31] Particularly, Andrejeva and Volkova emphasized the importance of understanding patient needs when setting appropriate goals. 29 These aspects involved the process of organizing information based on collected data, hence categorized under information gathering and organization.…”
Section: Information Gathering and Organizationmentioning
confidence: 99%